Sistem Informasi Pengelolaan Manajemen Hotel pada Hotel Planet Holiday Berbasis Web Mobile - Dwiputri Permatasari, Ririt; Paulina Suri, Ghea; Marchiano, Herli; Saputra, Tommy (CV. Publikasi Indonesia, 2022)
This study aims to design a mobile web-based hotel management information system at Planet Holiday Hotels, the background of this research is for problems that often occur in the management structure of Planet Holiday Hotels, namely the placement and compilation of data collection that is less than optimal at the time of the recap of employee data collection in position or department data so that the positions that are already full are entered into the Planet Holiday Hotel data collection which has various departments where there will be a data crosscheck process, they have to wait for the next data collection which will take a long time. The stages are literature study, data collection, data processing, system design, implementation, testing and deployment. Meanwhile, the method and modeling used is the Rational Unfield Process (RUP) and the modeling is using the Unfield Modeling Language (UML). This information system is designed based on a mobile web made with Process Hypertext Preprocessor (PHP), Cascading Style Sheet (CSS) technology, which was built using Xampp as a web server. With the existence of a management structure information system at Hotel Planet Holiday, it is hoped that the results of the research carried out can be concluded that it can help media information management become easier, system managers such as Human Resources can easily manage data collection and also employee data can be viewed in a timely manner. The management structure information system at Planet Holiday Hotel is expected to be able to collect data on the employee structure of the mobile web-based management structure information system so that it has a wider coverage and can help employees for efficient work programs.